IMF-Supported Programs in Indonesia, Korea and Thailand - Lane, Timothy (Occasional Papers; Occasional Paper ;, 1999)
This paper is a preliminary review of the design of and early experience with IMF-supported programs in Indonesia, Korea, and Thailand during 1997-98. The review takes into account developments as of October 1998, and was the basis for a discussion of the programs by the IMF's Executive Board in December 1998.